Development of Local Content Curriculum Based on The Merdeka Curriculum for High School in East Kalimantan Province - Nursafitri, Laila; Firdaus, Taman; Sudomo, R. Irlanto; Kurniasih, Apri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Local content subjects are highly needed, especially for the progress of regions that can positively impact national progress. This research aims to develop a Local Content Curriculum based on the Merdeka Curriculum for High Schools in East Kalimantan Province. The research method used is the development research steps from the Plomp model, namely 1) Investigation; 2) Design; 3) Realization/Construction; 4) Testing, Evaluating, and Revision. In addition, in curriculum development, this research uses the Understanding by Design (UbD) steps consisting of 1) Identifying desired results, 2) Determining Assessment Evidence, and 3) Plan Learning Experiences and Instruction. Data was collected through a literature review and focus group discussions (FGD). The instrument used in the FGD uses an open questionnaire. Curriculum validation was obtained through expert judgment using a validation questionnaire instrument. Qualitative data obtained were analyzed descriptively, while score data were analyzed and converted into assessment categories. This research produces a Local Content Curriculum based on the Merdeka Curriculum for High Schools in East Kalimantan Province, which falls into the Very Feasible category. Furthermore, the advantages and disadvantages of this curriculum product are discussed further in the article.